Reducing training frequency from 3 or 4 sessions/week to 2 sessions/week does not attenuate improvements in maximal aerobic capacity with reduced-exertion high-intensity interval training (REHIT) - Richard Metcalfe (Applied Physiology, Nutrition, and Metabolism, 2020)
In the present randomised-controlled trial we investigated the effect of REHIT training frequency (2/3/4 sessions/week for 6 weeks) on maximal aerobic capacity (V̇O2max) in 42 inactive individuals (13 women; mean±SD age: 25±5 y, V̇O2max: 35±5 mL·kg-1·min-1). Changes in V̇O2max were not significantly different between the three groups (2 sessions/week: +10.2%; 3 sessions/week: +8.1%; 4 sessions per week: +7.3%). In conclusion, a training frequency of 2 sessions/week is sufficient for REHIT to improve V̇O2max. Novelty: • We demonstrate that reducing REHIT training frequency from 3 or 4 to 2 sessions/week does not attenuate improvements in the key health marker of V̇O2max.